(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
Education and its commitment to society are one of the topics that have been extensively discussed in recent years. In general terms, a large portion of the debates have stemmed from the complaints of those students who perceive that educational institutions do not adequately prepare them for active life. In this sense, there are numerous writers, especially in essays but also in novels, who have reflected on the educational landscape and consequently presented a critical view of it. They delve not only into generalities but also into specific issues they perceive as vital for the proper functioning of education within their respective territories."